Grain boundary coating method of polycrystalline positive electrode material and grain boundary coated polycrystalline positive electrode material
By using chemical reaction of gas-phase reaction source in a tube furnace, dense grain boundary coating of polycrystalline cathode material is achieved, and the problems of uneven coating and performance in the prior art are solved, and the stability and electricality of the battery are improved. Chemical performance, suitable for high-energy and high-power battery needs.
Patent Information
- Application Number
- CN202411185249.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-13
AI Technical Summary
The existing technology is difficult to achieve dense grain boundary coating of polycrystalline cathode materials, resulting in degradation of material performance and unstable battery performance. Especially during storage and preparation, the surface activity is high, easy to react with air and electrolyte, forming residual alkali and Side reactions, destroying the material structure.
The gas-phase reaction source is carried out using a tube furnace to perform chemical reactions, and the reaction source diffuses along the grain boundary through the pressure of the gas flow to form a cladding layer. The specific steps include heating the polycrystalline positive electrode material in the furnace tube and alternately passing into different gas-phase reaction sources and carrier gas. , control the airflow pressure between 0.15-0.3Mpa to ensure that the reaction source permeates into the grain boundary and forms a uniform and dense grain boundary cladding layer.
The uniform grain boundary coating of polycrystalline cathode material is achieved, the stability and electrochemical performance of the material are improved, the contact with the electrolyte is reduced, the battery life is extended, and it is suitable for large-scale commercial production, and it is cheap.
Smart Images

Figure CN119133387A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage materials, and in particular relates to a grain boundary coating method for a polycrystalline positive electrode material and a grain boundary coated polycrystalline positive electrode material. Background Art
[0002] Under the guidance of the "carbon peak and carbon neutrality" goals, sustainable development energies such as solar energy, wind energy and ocean energy have been widely used. However, these energies will change with natural conditions and have problems such as wide distribution and intermittent nature. Secondary batteries have gradually replaced pumped storage and become an important new energy storage method due to their advantages such as flexible site selection and wide range of applications. At the same time, the development of portable electronic devices and electric vehicles has also put forward higher requirements on the energy density and power density of batteries. Positive electrode materials with excellent performance are the core components that determine battery performance, and the synthesis and preparation of materials dominate the research and development of battery materials. Therefore, the present invention proposes a preparation and synthesis method for grain boundary coating of polycrystalline battery positive electrode materials to promote the development of high-energy, high-power, high-safety and long-life secondary batteries.
[0003] At present, whether it is a lithium-ion battery system or a sodium-ion battery system, the research and development of battery materials for commercialization mainly revolves around multi-element polycrystalline positive electrode materials. However, the positive electrode materials have high surface activity and are easily exposed to H in the air during storage and preparation. 2 O and CO 2 The reaction forms residual alkali, resulting in loss of reversible capacity. In addition, the surface of the positive electrode material is very likely to undergo side reactions with the electrolyte, deteriorating the performance of the polycrystalline positive electrode material and destroying the surface structure of the material. At the same time, during the cycle, the electrolyte will penetrate into the material along the microcracks, aggravating the deterioration of the material. Surface coating is an effective modification strategy that effectively improves the performance of polycrystalline positive electrode materials by constructing a protective layer on the surface. In previous reports, people have used a variety of synthesis processes to coat the coating layer on the surface of secondary particles, and then form grain boundary coating or surface doping through secondary calcination or annealing. However, most of the current methods are relatively cumbersome and cannot form a dense grain boundary coating layer.
[0004] Using chemical vapor deposition technology (ALD) to achieve surface coating is one of the methods to improve the interface stability of high-nickel materials. The patent document with publication number CN115775879A uses the atomic layer deposition method to coat the LZSP solid electrolyte layer, so that it is evenly and densely deposited on the surface of the core particles, thereby stabilizing the electrode electrolyte interface and improving the lithium ion diffusion coefficient. However, the coating layer synthesized by this method only exists on the surface of the particles and cannot achieve grain boundary coating because ALD is preferentially deposited on the surface of the particles.
[0005] The patent document with publication number CN102244231A uses atomic layer deposition technology to deposit surface modification substances on the surface of the positive electrode active material of the lithium battery or the surface of the positive electrode to achieve the effect of coating, specifically including the introduction of gas phase precursors to achieve surface coating, thereby improving the performance of the material. However, this method also cannot achieve the effect of grain boundary coating, because the introduced gas phase precursor will preferentially deposit on the particle surface under normal pressure, and will not diffuse into the grain boundary. Once an atomic deposition layer is formed on the particle surface, subsequent deposition will not enter the grain boundary. Summary of the invention
[0006] The present invention provides a method for grain boundary coating of polycrystalline positive electrode materials and grain boundary coated polycrystalline positive electrode materials, so that a gas phase reaction source chemically reacts on the surface of primary particles of the polycrystalline positive electrode material to form a required grain boundary coating layer, thereby overcoming the defects of the prior art such as uneven coating and inability to directly coat primary particles.
[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0008] A method for coating grain boundaries of polycrystalline positive electrode materials comprises the following steps: placing the polycrystalline positive electrode materials in a tube of a tubular furnace for heating, diffusing a gas phase reaction source into the polycrystalline positive electrode materials along grain boundaries under the action of gas flow pressure, reacting the gas phase reaction source on the surface and grain boundaries of the polycrystalline positive electrode materials to form a coating layer on the surface and grain boundaries of the polycrystalline positive electrode materials, and obtaining a grain boundary coated polycrystalline positive electrode material.
[0009] Preferably, the gas flow pressure is 0.15-0.3Mpa. Specifically, the gas flow pressure mainly comes from the gas flow pressure of the gas phase reaction source introduced into the furnace tube, the gas flow pressure of the carrier gas introduced into the furnace tube, or the gas flow pressure of the mixed gas of the gas phase reaction source and the carrier gas introduced into the furnace tube; the carrier gas includes one or more of an inert gas and nitrogen;
[0010] The gas flow pressure of the gas-phase reaction source introduced into the furnace tube is 0.15-0.3Mpa; the gas flow pressure of the carrier gas introduced into the furnace tube is 0.15-0.3Mpa; the gas flow pressure of the mixed gas of the gas-phase reaction source and the carrier gas introduced into the furnace tube is 0.15-0.3Mpa. If the gas flow pressure is too small, it cannot ensure that the gas-phase reaction source penetrates into the grain boundary of the polycrystalline positive electrode material, and it is only a surface coating form; if the gas flow pressure is too large, it may cause the reactants to be blown out of the tubular furnace, and may also cause the tubular furnace to rupture, and increase the consumption of reactants. And the gas flow pressure can also control the gas diffusion rate, thereby affecting the growth rate of the coating layer.
[0011] In the present invention, a furnace tube of the tubular furnace is provided with an air inlet at one end along the length direction and an air outlet at the other end; a gas phase reaction source, a carrier gas, or a mixed gas of the gas phase reaction source and the carrier gas providing gas flow pressure is introduced from the air inlet of the furnace tube.
[0012] Preferably, the coating layer includes one or more of metal oxides, fast ion conductors, polyanion compounds, and fluorides.
[0013] Preferably, the metal oxide comprises TiO 2 、Al 2 O 3 、ZrO 2 , ZnO; the fast ion conductor includes Li 2 MoO 4 、LiAlO 2 One or more of; the polyanion compound includes Li 3 PO 4 ; The fluoride includes LiF, FeF 3 One or more of .
[0014] Preferably, the grain boundary coating method of the polycrystalline positive electrode material specifically comprises the following steps:
[0015] (1) placing a polycrystalline positive electrode material in a tube of a tube furnace and heating it;
[0016] (2) firstly introduce a first gas phase reaction source or a mixed gas of the first gas phase reaction source and a carrier gas into the furnace tube, so that the first gas phase reaction source is adsorbed on the surface and grain boundaries of the polycrystalline positive electrode material; wherein the gas flow pressure of the first gas phase reaction source or the mixed gas flow pressure of the first gas phase reaction source and the carrier gas is 0.15-0.3 MPa;
[0017] (3) using an inert gas or nitrogen to remove the first gas phase reaction source in the furnace tube;
[0018] (4) Then, a second gas phase reaction source or a mixed gas of the second gas phase reaction source and a carrier gas is introduced, and the second gas phase reaction source reacts with the first gas phase reaction source on the surface and grain boundaries of the polycrystalline positive electrode material; wherein the gas flow pressure of the second gas phase reaction source or the gas flow pressure of the mixed gas of the second gas phase reaction source and the carrier gas is 0.15-0.3 MPa;
[0019] (5) using an inert gas or nitrogen to remove the second gas phase reaction source in the furnace tube;
[0020] (6) Repeat steps (2) to (5) multiple times; after the reaction is completed, a grain boundary coated polycrystalline positive electrode material is obtained.
[0021] The above method of the present invention is suitable for crystal coating involving multiple chemical reaction processes, so different gas phase reaction sources need to be introduced alternately. Before the different gas phase reaction sources are introduced alternately, an inert gas or nitrogen can be introduced to remove the remaining gas phase reaction sources from the previous reaction. After the first gas phase reaction source and the second gas phase reaction source with gas flow pressure enter the furnace tube of the tubular furnace, they can quickly diffuse into the grain boundary of the material and fully contact with the grain boundary on the surface of the material.
[0022] The grain boundary coating layer synthesized by the chemical reaction of the present invention has good stability and low reactivity, and will not decompose under heat or react with other substances. Figure 1 The device shown.
[0023] The first gas phase reaction source includes water vapor, O 3 One or more of the above, wherein the second gas phase reaction source comprises titanium tetraisopropoxide gas, Al(CH 3 ) 3 Gas, TiCl 4 Gas, TiI 4 Gas, AlCl 3 Gas, ZrCl 4 gas, diethyl zinc gas or one or more thereof; and / or the first gas phase reaction source comprises lithium tert-butoxide gas, the second gas phase reaction source comprises Al(CH 3 ) 3 Gas, MoCl 5 One or more of the gases;
[0024] The carrier gas includes one or more of nitrogen and inert gas; the heating temperature in the tube of the tube furnace is 100-700°C; for the above-mentioned reaction gas, it is necessary to control the temperature of the tube furnace to regulate the temperature required for the chemical reaction. The specific temperature is determined by the specific reaction mechanism, and the required coating layer can be generated on the grain boundary and the surface.
[0025] Preferably, in step (1), the rotation of the furnace tube of the tubular furnace is controlled; in step (2), the time for introducing the first gas-phase reaction source or the mixed gas of the first gas-phase reaction source and the carrier gas is 3-5 s; in step (3), the time for clearing the first gas-phase reaction source in the furnace tube with an inert gas or nitrogen is 10-60 s; in step (4), the time for introducing the second gas-phase reaction source or the mixed gas of the second gas-phase reaction source and the carrier gas is 3-5 s; in step (5), the time for clearing the second gas-phase reaction source in the furnace tube of the tubular furnace with an inert gas or nitrogen is 10-60 s.
[0026] The present invention controls the contact time between the gas phase reaction source and the polycrystalline positive electrode material within a suitable range, thereby effectively ensuring the quality and continuity of the surface coating film.
[0027] Preferably, the grain boundary coating method of the polycrystalline positive electrode material may further specifically include the following steps:
[0028] A chemical precursor and a polycrystalline positive electrode material are placed in a furnace tube of a tubular furnace and heated. The chemical precursor is decomposed by heat to produce a first gas phase reaction source. A carrier gas, a second gas phase reaction source, or a mixture of the carrier gas and the second gas phase reaction source are introduced into the furnace tube. The first gas phase reaction source, or a mixture of the first gas phase reaction source and the second gas phase reaction source, undergoes a gas-solid reaction on the surface and grain boundaries of the polycrystalline positive electrode material, so that a coating layer is formed on the surface and grain boundaries of the polycrystalline positive electrode material, and a grain boundary coated polycrystalline positive electrode material is obtained; wherein the gas flow pressure of the carrier gas, the second gas phase reaction source, or the mixture of the carrier gas and the second gas phase reaction source is 0.15-0.3Mpa.
[0029] In this method, the coating layer formed does not require multiple chemical reaction processes and can occur continuously on the surface. This method can directly obtain a coated sample that completely covers the grain boundary, isolating the positive electrode material from the electrolyte to the greatest extent. In addition, this method is simple to operate, low in price, and easy to implement, suitable for large-scale commercial production, and the synthesized samples can meet the needs of high-energy and high-power batteries.
[0030] The above method is suitable for crystal coating that does not involve multiple chemical reactions, and the reaction can continue on the surface. The gas introduced during the above ventilation can be used as a reaction gas or not participate in the reaction. Its main function is to make the gas phase reaction source contact with the polycrystalline positive electrode material. The grain boundary and surface of the polycrystalline positive electrode material have capture capabilities, and the grain boundary coating layer synthesized by the reaction has low reactivity. The above grain boundary coating method can be used in specific implementation. Figure 2 Or the device shown in 3.
[0031] Preferably, the chemical precursor includes one or more of ammonium bifluoride and ammonium dihydrogen phosphate; the chemical precursor can be decomposed into the required gas phase reaction source and will not be decomposed again when reaching the surface of the material; the carrier gas includes one or more of inert gas and nitrogen; the second gas phase reaction source is consistent with or different from the first gas phase reaction source in composition;
[0032] The mass ratio of the chemical precursor to the polycrystalline positive electrode material is 1:50-150;
[0033] The heating temperature is 100-250° C., and the reaction time is 200-500 min.
[0034] The present invention controls the temperature, time, amount of chemical precursor and gas flow rate within the above range, so that the grain boundary coating layer has good quality and continuity and a suitable thickness.
[0035] Preferably, heating the chemical precursor and the polycrystalline cathode material in the furnace tube of a tube furnace means heating the chemical precursor and the polycrystalline cathode material after mixing them in the furnace tube of the tube furnace (which can be carried out as shown in Figure 2 ), or heating the chemical precursor and the polycrystalline cathode material separately in the furnace tube of the tube furnace (which can be carried out as shown in Figure 3 ). And the chemical precursor is located between the gas inlet of the tube furnace and the polycrystalline cathode material. Specifically, in this method, the chemical precursor is placed at the gas inlet in the tube furnace, and the polycrystalline cathode material is placed in the boat in the furnace tube in the tube furnace for heating.
[0036] Preferably, the general formula of the polycrystalline cathode material is A x BO 2 , where A is Li and 0 < x ≤ 1; B is one or more of Ni, Mn, Co, Fe, and Cu; the polycrystalline cathode material is secondary spherical-like particles composed of primary particles, and there are grain boundaries between the primary particles.
[0037] As a general inventive concept, the present invention also provides a grain boundary-coated polycrystalline cathode material prepared by the above grain boundary coating method.
[0038] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0039] The method of the present invention utilizes the characteristics that the gas-phase reaction source molecules are small and the gaps between the secondary particles of the polycrystalline cathode material are large. By combining the control of the gas flow pressure of the gas-phase reaction source, etc., it can be realized that the gas-phase reaction source instantaneously fills the gaps between the secondary particles of the polycrystalline cathode material. Combined with an appropriate reaction temperature, chemical reactions occur on the surface and grain boundaries of the polycrystalline cathode material to obtain a grain boundary-coated polycrystalline cathode material.
[0040] Moreover, when the present invention prepares the grain boundary-coated polycrystalline cathode material, it directly uses a tube furnace for preparation. The device is simple. Combined with the method in the present invention, uniform grain boundary coating can be realized, and the cost is low. There is no need to use a costly ALD reactor. And when using the tube furnace of the present invention to prepare the grain boundary-coated polycrystalline cathode material, the gas-phase reaction source and the polycrystalline cathode material can be more fully contacted. For example, when the chemical precursor and the cathode material are mixed and heated, the molten residual lithium on the surface will bring the chemical precursor into the grain boundaries. At this time, introducing a carrier gas can realize in-situ grain boundary coating.
[0041] The present invention can introduce functional groups capable of capturing the gas-phase reaction source at the grain boundaries of the polycrystalline cathode material as much as possible, which is more conducive to realizing grain boundary coating. In addition, in the method of the present invention, the vaporizable coating is mixed with the material in the solid state, which increases the contact area. Compared with only introducing the gas-phase reaction source for coating, the amount of the coating material is greatly reduced, and the cost is lowered.
[0042] The present invention can directly obtain a completely coated grain boundary coated polycrystalline positive electrode material, and the grain boundary coated polycrystalline positive electrode material can minimize the contact between the polycrystalline positive electrode material and the electrolyte, thereby improving the electrochemical performance of the multi-element positive electrode material. The present invention overcomes the defects of the prior art such as uneven coating and inability to directly perform a single particle coating.
[0043] The method of the invention is simple to operate, low in price, extremely easy to implement and suitable for large-scale commercial production, and the synthesized product can meet the demand for high-energy and high-power batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 Schematic diagram of the structure of the device used in the grain boundary coating method of the present invention Figure 1 ;
[0046] Figure 2 Schematic diagram of the structure of the device used in the grain boundary coating method of the present invention Figure 2 ;
[0047] Figure 3 Schematic diagram of the structure of the device used in the grain boundary coating method of the present invention Figure 3 ;
[0048] Figure 4 This is the XRD pattern of the grain boundary coated polycrystalline positive electrode material prepared in Example 1 of the present invention;
[0049] Figure 5 This is a SEM image of the grain boundary coated polycrystalline positive electrode material prepared in Example 1 of the present invention;
[0050] Figure 6 This is a SEM image of the original polycrystalline positive electrode material in Example 1 of the present invention;
[0051] Figure 7 The cross-sectional TEM image of the grain boundary coated polycrystalline positive electrode material prepared in Example 1 of the present invention and the corresponding element EDS image;
[0052] Figure 8 This is a comparison chart of the electrochemical performance of the grain boundary coated polycrystalline positive electrode material and the original polycrystalline positive electrode material prepared in Example 1 of the present invention.
[0053] Fig. 9The cross-sectional TEM image of the grain boundary coated polycrystalline positive electrode material prepared in Example 3 of the present invention and the EDS mapping image of the corresponding elements. DETAILED DESCRIPTION
[0054] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0055] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0056] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0057] In the following Examples 1-3 and Comparative Examples 1-2, the polycrystalline positive electrode materials used are all secondary spherical particles composed of primary particles. There are grain boundaries between the primary particles, and the secondary particles have a relatively regular spherical morphology with a particle size of about 4-12 μm.
[0058] Embodiment 1:
[0059] A method for coating grain boundaries of a polycrystalline positive electrode material comprises the following steps:
[0060] (1) Using high nickel multi-element positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O 2 The polycrystalline positive electrode material is a polycrystalline positive electrode material. 10 g of the polycrystalline positive electrode material is placed in a tube of a tubular furnace and heated to 250° C. The tube of the tubular furnace is controlled to rotate at a speed of 30 r / min. An air inlet is provided at one end of the tube of the tubular furnace along the length direction, and an air outlet is provided at the other end.
[0061] (2) First, water vapor is introduced from the air inlet of the furnace tube to allow the water vapor to adsorb onto the surface of the polycrystalline positive electrode material and its grain boundaries; wherein the air flow pressure of the water vapor is 0.2 MPa, the air flow rate is 1 L / min, and the time for introducing the water vapor is 3 s;
[0062] (3) Using nitrogen to remove water vapor in the tube of the tube furnace for 40 seconds;
[0063] (4) Then, titanium tetraisopropoxide gas is introduced from the air inlet of the furnace tube, and the titanium tetraisopropoxide gas reacts with water on the surface of the polycrystalline positive electrode material and at its grain boundaries; wherein the air flow pressure of the titanium tetraisopropoxide gas is 0.2 MPa, the air flow rate is 1 L / min, and the time for introducing the titanium tetraisopropoxide gas is 3 s;
[0064] (5) using nitrogen to purge titanium tetraisopropoxide gas in the tube of the tube furnace for 30 seconds;
[0065] (6) Repeat steps (2)-(5) 600 times; after the reaction is completed, TiO 2 Grain boundaries coated with polycrystalline cathode material.
[0066] Figure 4 , Figure 5 They are respectively the XRD and SEM images of the grain boundary coated polycrystalline positive electrode material of this embodiment, Figure 6 This is the SEM image of the original polycrystalline positive electrode material of this embodiment. It can be seen from the figure that the morphology and structure of the material before and after coating have not changed significantly. 2 It exists in an amorphous state on the particle surface.
[0067] Figure 7 The cross-sectional TEM image of the grain boundary coated polycrystalline positive electrode material and the corresponding element EDS mapping image are shown in the figure. It can be seen from the figure that Ti is evenly distributed in the grain boundary. This is effective evidence that the grain boundary coating method of the polycrystalline positive electrode material of the present invention can be implemented.
[0068] The grain boundary coated polycrystalline positive electrode material prepared in Example 1 and the original polycrystalline positive electrode material were used as positive electrode materials, and the active material: conductive carbon black: polyvinylidene fluoride (PVDF) were uniformly mixed and stirred in N-methylpyrrolidone (NMP) medium at a mass ratio of 8:1:1 to form a slurry, and then the slurry was uniformly coated on an aluminum foil using a scraper, and a disc with a diameter of 12 mm was obtained after drying and sheeting. Metal lithium was then used as the negative electrode to assemble a button cell for electrochemical testing. Figure 8 The electrochemical performance comparison diagram of the grain boundary coated polycrystalline positive electrode material prepared in this embodiment and the original polycrystalline positive electrode material shows that the capacity retention rate of the grain boundary coated polycrystalline positive electrode material is close to 100% after 200 cycles at a current density of 1C. Figure 8 It can be seen that the samples coated with grain boundaries have better electrochemical performance.
[0069] Embodiment 2:
[0070] A method for coating grain boundaries of a polycrystalline positive electrode material comprises the following steps:
[0071] Ammonium bifluoride with a mass ratio of 1:100 and polycrystalline positive electrode material LiCoO 2The mixture is placed in the tube of a tube furnace, the furnace temperature is set to 180°C, and the heat preservation time is 300 minutes. The tube of the tube furnace is provided with an air inlet at one end along the length direction and an air outlet at the other end. During the heating process, nitrogen is introduced into the tube of the tube furnace from the air inlet of the furnace tube. At high temperature, ammonium bifluoride is decomposed into NH 3 Driven by nitrogen, HF diffuses into the polycrystalline positive electrode material along the grain boundary, and HF undergoes a gas-solid reaction on the surface and grain boundary of the polycrystalline positive electrode material to prepare a lithium fluoride grain boundary coated polycrystalline positive electrode material. The nitrogen gas flow pressure is 0.18Mpa and the gas flow rate is 1.5L / min.
[0072] Embodiment 3:
[0073] A method for coating grain boundaries of a polycrystalline positive electrode material comprises the following steps:
[0074] Place ammonium dihydrogen phosphate into the air inlet of the tube furnace tube, and add polycrystalline positive electrode material LiNiO 2 Lay flat in the furnace boat of the tube furnace, diammonium phosphate and polycrystalline positive electrode material LiNiO 2 The mass ratio is 1:80, the furnace temperature is set to 200℃, and the insulation time is 200min. The tube of the tube furnace is provided with an air inlet at one end along the length direction and an air outlet at the other end. During the heating process, argon gas is introduced into the tube of the tube furnace from the air inlet of the furnace tube. At high temperature, ammonium dihydrogen phosphate is thermally decomposed to produce phosphine, water vapor and oxygen. Driven by argon gas, phosphine diffuses into the polycrystalline positive electrode material along the grain boundary. Phosphine reacts with the surface and grain boundary of the polycrystalline positive electrode material to form a lithium phosphate grain boundary coated polycrystalline positive electrode material. The gas flow pressure of the carrier gas argon is 0.3Mpa, and the gas flow rate is 2L / min.
[0075] Fig. 9 The cross-sectional TEM and corresponding element EDS mapping diagram of the grain boundary coated polycrystalline positive electrode material of this embodiment. It can be seen from the figure that P is evenly distributed in the grain boundary.
[0076] Comparative Example 1:
[0077] A method for grain boundary coating of a polycrystalline positive electrode material, which differs from Example 1 only in that the gas phase reaction source introduced is at a conventional pressure, specifically comprising the following steps:
[0078] (1) Using high nickel multi-element positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O 2The polycrystalline positive electrode material is a polycrystalline positive electrode material. 10 g of the polycrystalline positive electrode material is placed in a tube of a tubular furnace and heated to 250° C. The tube of the tubular furnace is controlled to rotate at a speed of 30 r / min. An air inlet is provided at one end of the tube of the tubular furnace along the length direction, and an air outlet is provided at the other end.
[0079] (2) First, water vapor is introduced from the air inlet of the furnace tube. The air flow pressure of the water vapor is 0.1 MPa, the air flow rate is 1 L / min, and the time of introducing the water vapor is 3 s;
[0080] (3) Using nitrogen to remove water vapor in the tube of the tube furnace for 40 seconds;
[0081] (4) Then, titanium tetraisopropoxide gas was introduced from the air inlet of the furnace tube, the air flow pressure of the titanium tetraisopropoxide gas was 0.1 MPa, the air flow rate was 1 L / min, and the time of introducing the titanium tetraisopropoxide gas was 3 s;
[0082] (5) using nitrogen to purge titanium tetraisopropoxide gas in the tube of the tube furnace for 30 seconds;
[0083] (6) Repeat steps (2)-(5) 600 times; after the reaction is completed, TiO 2 Coating material.
[0084] The TiO prepared in Comparative Example 1 2 The coating material is used as the positive electrode material. The active material: conductive carbon black: polyvinylidene fluoride (PVDF) is uniformly mixed and stirred into a slurry in an N-methylpyrrolidone (NMP) medium at a mass ratio of 8:1:1, and then evenly coated on an aluminum foil with a scraper. After drying and sheeting, a disc with a diameter of 12 mm is obtained. Metal lithium is then used as the negative electrode and assembled into a button cell for electrochemical testing. After 100 cycles at a current density of 1C, the capacity retention rate is only 87.22%, which is significantly lower than the polycrystalline positive electrode material modified by uniform grain boundary coating prepared in Example 1.
[0085] Comparative Example 2:
[0086] A method for grain boundary coating of a polycrystalline positive electrode material, which differs from Example 2 only in that no carrier gas is introduced, comprises the following steps:
[0087] Ammonium bifluoride with a mass ratio of 1:100 and polycrystalline positive electrode material LiCoO 2 The mixture was placed in a tube furnace, the furnace temperature was set to 180°C, the insulation time was 300 min, and no carrier gas was introduced. During the heating process, ammonium bifluoride was decomposed into NH 3 and HF to prepare lithium fluoride coated material.
[0088] A button-type half-cell assembled with polycrystalline positive electrode materials was prepared, and the lithium fluoride grain boundary coated polycrystalline positive electrode material in Example 2, the lithium phosphate grain boundary coated polycrystalline positive electrode material in Example 3, and the original polycrystalline positive electrode material LiCoO in Example 2 were tested. 2 , the original polycrystalline positive electrode material LiNiO in Example 3 2 , the electrochemical properties of the lithium fluoride coated material in Comparative Example 2, Table 1 is the electrochemical performance test data of each positive electrode material at different current densities in the voltage range of 2.7-4.3V.
[0089] Table 1 Electrochemical performance test results of various cathode materials at different current densities
[0090]
[0091] It can be seen from Table 1 that the lithium fluoride grain boundary coated polycrystalline positive electrode material and the polycrystalline positive electrode material LiCoO in Example 2 2 Comparison, and Example 3, lithium phosphate grain boundary coated polycrystalline positive electrode material and polycrystalline positive electrode material LiNiO 2 By comparison, it can be seen that the present invention obtains a grain boundary coated polycrystalline positive electrode material by a gas-solid reaction between a gas phase reaction source and the surface and grain boundaries of a polycrystalline positive electrode material, which can isolate the polycrystalline positive electrode material from contact with the electrolyte to the greatest extent and improve the electrochemical performance of a polycrystalline positive electrode battery. By comparing the lithium fluoride grain boundary coated polycrystalline positive electrode material in Example 2 with the lithium fluoride coated material in Comparative Example 2, it can be seen that the discharge specific capacity of the lithium fluoride coated material in Comparative Example 2 is only 210.82 mAh / g, and the capacity retention rate of 1C cycle 100 cycles is only 72.93%, which is significantly lower than the lithium fluoride grain boundary coated polycrystalline positive electrode material prepared in Example 2.
[0092] The above combined with the accompanying drawings are preferred embodiments of the present invention, but the present invention is not limited to the described embodiments. It should be pointed out that for those skilled in the art, without departing from the principles of the present invention, changes, improvements and modifications to these embodiments should be considered as the protection scope of the present invention.
Claims
1. A method for grain boundary coating of a polycrystalline positive electrode material, characterized in that: The following steps are involved: The polycrystalline positive electrode material is placed in the furnace tube of a tubular furnace and heated. The gas phase reaction source diffuses into the polycrystalline positive electrode material along the grain boundary under the action of the airflow pressure. The gas phase reaction source reacts on the surface and grain boundary of the polycrystalline positive electrode material to form a coating layer on the surface and grain boundary of the polycrystalline positive electrode material, thereby obtaining a grain boundary coated polycrystalline positive electrode material.
2. The method for grain boundary coating of polycrystalline positive electrode material according to claim 1, characterized in that: The gas flow pressure mainly comes from the gas flow pressure of the gas phase reaction source introduced into the furnace tube, the gas flow pressure of the carrier gas introduced into the furnace tube, or the gas flow pressure of the mixed gas of the gas phase reaction source and the carrier gas introduced into the furnace tube; the carrier gas includes one or more of an inert gas and nitrogen; The gas flow pressure of the gas phase reaction source introduced into the furnace tube is 0.15-0.3Mpa; the gas flow pressure of the carrier gas introduced into the furnace tube is 0.15-0.3Mpa; the gas flow pressure of the mixed gas of the gas phase reaction source and the carrier gas introduced into the furnace tube is 0.15-0.3Mpa.
3. The grain boundary coating method of polycrystalline positive electrode material according to claim 1, characterized in that: The coating layer includes one or more of metal oxides, fast ion conductors, polyanion compounds, and fluorides.
4. The method for grain boundary coating of polycrystalline positive electrode material according to claim 3, characterized in that: The metal oxide includes one or more of TiO2, Al2O3, ZrO2, and ZnO; the fast ion conductor includes one or more of Li2MoO4 and LiAlO2; the polyanion compound includes Li3PO4; and the fluoride includes one or more of LiF and FeF3.
5. The method for grain boundary coating of a polycrystalline positive electrode material according to any one of claims 1 to 4, characterized in that: The specific steps include: (1) placing a polycrystalline positive electrode material in a tube of a tube furnace and heating it; (2) firstly introduce a first gas phase reaction source or a mixed gas of the first gas phase reaction source and a carrier gas into the furnace tube, so that the first gas phase reaction source is adsorbed on the surface and grain boundaries of the polycrystalline positive electrode material; wherein the gas flow pressure of the first gas phase reaction source or the mixed gas flow pressure of the first gas phase reaction source and the carrier gas is 0.15-0.3 MPa; (3) using an inert gas or nitrogen to remove the first gas phase reaction source in the furnace tube; (4) Then, a second gas phase reaction source or a mixed gas of the second gas phase reaction source and a carrier gas is introduced, and the second gas phase reaction source reacts with the first gas phase reaction source on the surface and grain boundaries of the polycrystalline positive electrode material; wherein the gas flow pressure of the second gas phase reaction source or the gas flow pressure of the mixed gas of the second gas phase reaction source and the carrier gas is 0.15-0.3 MPa; (5) using an inert gas or nitrogen to remove the second gas phase reaction source in the furnace tube; (6) Repeat steps (2) to (5) multiple times; after the reaction is completed, a grain boundary coated polycrystalline positive electrode material is obtained.
6. The method for grain boundary coating of polycrystalline positive electrode material according to claim 5, characterized in that: The first gas-phase reaction source includes one or more of water vapor and O3, and the second gas-phase reaction source includes one or more of titanium tetraisopropoxide gas, Al(CH3)3 gas, TiCl4 gas, TiI4 gas, AlCl3 gas, ZrCl4 gas, and diethyl zinc gas; and / or the first gas-phase reaction source includes lithium tert-butoxide gas, and the second gas-phase reaction source includes one or more of Al(CH3)3 gas and MoCl5 gas; The heating temperature in the tube of the tube furnace is 100-700°C.
7. The method for grain boundary coating of polycrystalline positive electrode material according to claim 5, characterized in that: In step (1), the furnace tube of the tubular furnace is controlled to rotate; in step (2), the time for introducing the first gas phase reaction source or the mixed gas of the first gas phase reaction source and the carrier gas is 3-5 seconds; in step (3), the time for clearing the first gas phase reaction source in the furnace tube with an inert gas or nitrogen is 10-60 seconds; in step (4), the time for introducing the second gas phase reaction source or the mixed gas of the second gas phase reaction source and the carrier gas is 3-5 seconds; in step (5), the time for clearing the second gas phase reaction source in the furnace tube of the tubular furnace with an inert gas or nitrogen is 10-60 seconds.
8. The method for grain boundary coating of a polycrystalline positive electrode material according to any one of claims 1 to 4, characterized in that: The specific steps include: A chemical precursor and a polycrystalline positive electrode material are placed in a furnace tube of a tubular furnace and heated. The chemical precursor is decomposed by heat to produce a first gas phase reaction source. A carrier gas, a second gas phase reaction source, or a mixture of the carrier gas and the second gas phase reaction source are introduced into the furnace tube. The first gas phase reaction source, or a mixture of the first gas phase reaction source and the second gas phase reaction source, undergoes a gas-solid reaction on the surface and grain boundaries of the polycrystalline positive electrode material, so that a coating layer is formed on the surface and grain boundaries of the polycrystalline positive electrode material, and a grain boundary coated polycrystalline positive electrode material is obtained; wherein the gas flow pressure of the carrier gas, the second gas phase reaction source, or the mixture of the carrier gas and the second gas phase reaction source is 0.15-0.3Mpa.
9. The method for grain boundary coating of polycrystalline positive electrode material according to claim 8, characterized in that: The chemical precursor includes one or more of ammonium bifluoride and ammonium dihydrogen phosphate; the second gas phase reaction source is consistent with or different from the first gas phase reaction source; The mass ratio of the chemical precursor to the polycrystalline positive electrode material is 1:50-150; The heating temperature is 100-250° C., and the reaction time is 200-500 min.
10. The method for grain boundary coating of polycrystalline positive electrode material according to claim 8, characterized in that: The step of placing the chemical precursor and the polycrystalline positive electrode material in the furnace tube of a tubular furnace for heating is to mix the chemical precursor and the polycrystalline positive electrode material and then place them in the furnace tube of a tubular furnace for heating, or to place the chemical precursor and the polycrystalline positive electrode material in the furnace tube of a tubular furnace for heating separately, and the chemical precursor is located between the air inlet of the furnace tube of the tubular furnace and the polycrystalline positive electrode material.
11. The method for grain boundary coating of polycrystalline positive electrode material according to claim 1, characterized in that: The general formula of the polycrystalline cathode material is A x BO2, where A is Li and 0 < x ≤ 1; B is one or more of Ni, Mn, Co, Fe, and Cu; the polycrystalline cathode material is a secondary spherical-like particle composed of primary particles, and there are grain boundaries between the primary particles.
12. A grain boundary coated polycrystalline positive electrode material, characterized in that: The material is prepared by the grain boundary coating method as described in any one of claims 1 to 11.
Citation Information
Patent Citations
Method for cladding surfaces of active material of anode and / or anode and methods manufacturing anode and battery
CN102244231A
High-nickel positive electrode material as well as preparation method and application thereof
CN115775879A
Cited By
Polycrystal positive electrode material and preparation method thereof, lithium ion battery and electric equipment
CN121617940A
Grain boundary coated positive electrode material as well as preparation method and application thereof
CN122393242A
